MENALAR KEMBALI HADITS DAN SHALAT TASBIH - Tujang, Bisri (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2013)
Tasbih prayer is prayer that has been believed by some Muslims, as recommended in Islamic prayer. it is based on the proposition that the hadith narrated by some scholars, such as imam Abu Daud, Tirmidhi and Ibn Majah, but after investigation of the side chains and Matn his law Tasbih prayer hadith is weak, even some scholars categorize into maudhuâ?? hadith (hadith false), as classified by the imam Ibn al-Jawzi in his book al-Maudhuu'aat, there are also those who say that this hadith, if it is authentic then surely maqluub (other matn confused with another isnaad or matn confused with another matn), as the opinion of Ibn Khuzaimah priest. Even Sheikhul Islam Ibn Taymiyyah said, that no one of the Imams of the four schools that encourage it, precisely imam Ahmad ibn Hanbal stated that the hadith is weak prayer beads. Kata Kunci: Hadits, Shalat, Tasbih, Hukum